1987
DOI: 10.1159/000242671
|View full text |Cite
|
Sign up to set email alerts
|

Heat Production and Respiratory Enzymes in Normal and Runt Newborn Piglets

Abstract: The heat productions of newborn runt and normal piglets were estimated over a range of ambient temperatures. Most runts increased their heat production in the cold, but when expressed as J·kg––0.67·min––1 it was significantly lower than in normal piglets (201.3 ± 16.0 and 144.7 ± 16.2 J·kg––0.67·min––1 for controls and runts, respectively, at 32 °C). Runts consequently had lower deep body temperatures (37.8 ± 0.2 and 36.8 ± 0.3 °C for controls and runts, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1988
1988
2004
2004

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Mechanisms by which this could be mediated are via the effects of thy roid hormones on respiratory enzymes and the lipid composition of the inner mitochon drial membrane [Brand and Murphy, 1987;Dauncey, 1990], Runt piglets have a lower resting metabolic rate (RMR) than controls both at thermal neutrality and in a cold envi ronment [Hayashi et al, 1987], At thermal neutrality, the RMR is determined at least in part by the efficiency of substrate oxidation and ADP phosphorylation. The increased proton motive force of hepatic mitochondria from hypothyroid rats [Hafner et al, 1988] suggests that at least part of the reduced RMR associated with low thyroid status stems from an alteration in mitochondrial heat production.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mechanisms by which this could be mediated are via the effects of thy roid hormones on respiratory enzymes and the lipid composition of the inner mitochon drial membrane [Brand and Murphy, 1987;Dauncey, 1990], Runt piglets have a lower resting metabolic rate (RMR) than controls both at thermal neutrality and in a cold envi ronment [Hayashi et al, 1987], At thermal neutrality, the RMR is determined at least in part by the efficiency of substrate oxidation and ADP phosphorylation. The increased proton motive force of hepatic mitochondria from hypothyroid rats [Hafner et al, 1988] suggests that at least part of the reduced RMR associated with low thyroid status stems from an alteration in mitochondrial heat production.…”
Section: Discussionmentioning
confidence: 99%
“…In this re spect. the lower respiratory enzyme activity in the skeletal muscle of newborn runts com pared with control littermates could be an important limiting factor [Hayashi et al, 1987], Thus, the lower metabolic capacity of the runts could be related to changes in mito chondrial structure and function resulting from the reduction in T3-receptor numbers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An SGA animal was defined provisionally as one with a birth weight of 0.8 kg or less, whereas the AGA littermates had birth weights of approximately 1.4 kg. Previous investigations had shown that, within the Institute herd, this method selects SGA as distinct from slightly small AGA animals (25). When birth weight is plotted against the cumulative sample proportion on normal probability paper, a litter without an SGA animal presents a single straight line, whereas SGA piglets appear as clear deviates from this line (26,27).…”
Section: Animalsmentioning
confidence: 99%
“…We asked whether IUGR influences renovascular, glomerular, or tubular responses to severe normocapnic hypoxemia. We used a morphometrically well-characterized state of asymmetrical IUGR in newborn piglets (3,17,41) and included animals with optimal vital conditions early after birth (10).…”
mentioning
confidence: 99%